Calves delay estrus cycles in postpartum cows by mechanisms other than suckling - S.D. Viker; G.H. Kiracofe (Kansas Agricultural Experiment Station Research Reports, 1990)
It is generally accepted that the suckling stimulus and the interactions between lactation and level of nutrition regulate the interval from calving to cycling in beef cows. However, rnastectomized cows (udder removed) kept with their calves had longer postpartum intervals to ovulation and estrus than mastectomized cows without calves. We conclude that ovulation and estrus can be suppressed by some cow-calf interaction that is independent of lactation and suckling.
Keywords: Cattlemen& #x27; s Day; 1990; Kansas Agricultural Experiment Station contribution; no. 90-361-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 592; Beef; Cows; Mastectomy; Postpartum intervals; Calf influence